PERBEDAAN PENGARUH BRAINGYM DAN LATIHAN KINESTETIK TERHADAP PROPIOCEPTIVE PADA ANAK USIA 4-6 TAHUN DI TPA AL MUSTAQIM - Veni Fatmawati; Siti Khotimah; Dika Rizki Imania (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2015)
The age of 4-6 years are the time for children to play so the best stimulationshould be implemented through games. They have not experienced the sensomotoricmaturation which affects concentration, posture, balance and daily behavior. It isnecessary to perform treatment as early as possible in the form of brain gym andkinesthetic exercises, which usually used both gross motoric skills and sensory. Thestudy aims to determine the effect of brain gym and kinesthetic exercises forproprioceptive in 4-6 years old children. The number of respondents of this study were48 children which were divided into 2 groups: group 1 with brain gym and group 2 withkinesthetic exercises. The treatment was routinely given 3 times a week for one month.The research method is a Quasi experimental research which was designed using preand post-test group design. Paired T test was the statistical test used for brain gym,Willcoxon test was used for kinesthetic exercises and Mann Whitney test was used fordifferent test influences. The results of the data analysis using paired T test shows thatthe p-value was 0.000 (p <0.05). This means that there is an influence of brain gym onproioseptive in 4-6 years old children at TPA Al Mustaqim. The data analysis test usingsig Wilcoxon rank test shows p-value of 0.000 (p <0.05), which means that there is aninfluence of kinesthetic exercises of proioseptive in 4-6 years old children at TPA AlMustaqim. The data analysis result using Mann Whitney Difference Test shows p valueof 0.787 (p> 0.05) which means that the difference in the effect of brain gym andkinesthetic exercises on propioceptive in 4-6 years old children at TPA Al Mustaqim. Itis suggested in 4-6 years old children are given braingym and kinesthetic exercises sothat propioceptive is increased and thus, the concentration, posture and balance of thechild is also improved.